Clinical Features of Patients With Spontaneous Intracranial Hypotension Complicated With Bilateral Subdural Fluid Collections. Issue 5 (15th April 2019) - Kim, Jang Hun; Roh, Haewon; Yoon, Won‐Ki; Kwon, Taek‐Hyun; Chong, Kyuha; Hwang, Soon‐Young; Kim, Jong Hyun
Abstract : Background: Subdural hygromas are often found bilaterally in spontaneous intracranial hypotension (SIH). They frequently progress to chronic subdural hematomas (CSDHs), and if the hematomas are formed, it is difficult to consider SIH as an underlying cause. Whether SIH is underlying or not among the patients presenting bilateral subdural fluid collections (hygromas or CSDHs) is clinically important because the treatment strategy should be different between them. Objectives: We designed a retrospective case‐control study to figure out differential clinical features of the patients presenting bilateral symptomatic subdural fluid collections owing to SIH. Methods: Sixty‐two patients with bilateral symptomatic subdural fluid collections were enrolled, and their data on general demographics, clinical courses, radiological findings, treatments, and outcomes were collected. The patients were divided into "SIH" and "Non‐SIH" groups, and a simple logistic regression analysis was performed to clarify the differences between the groups. The consequent receiver operating characteristics (ROC) curve analyses were performed with the significant predictors. Results: Eight patients (13%) were diagnosed with SIH. Young age (odds ratio [OR] = 0.831, 95% confidence interval [CI]: 0.743‐0.929, P  = .0012), no underlying disease (OR = 0.062, 95% CI: 0.007‐0.544, P  = .0121), radiological features of brain sagging (OR = 10.36, 95% CI: 0.912‐93.411, P  = .0017), pseudo‐subarachnoid hemorrhage (OR = 15.6, 95% CI: 2.088‐116.52, P  = .0074), and small amount of fluid collections (OR = 0.719, 95% CI: 0.579‐0.893, P  = .0029) were significantly associated with SIH group. ROC curve analyses were performed in parameters of age and amount of fluid collection and the cut‐off values for each parameter were ≤55 years old and ≤22.08 mm, respectively. Patients diagnosed with SIH underwent epidural blood patches and showed good results, except 1 patient who underwent burr‐hole trephinations. Conclusion: Bilateral subdural fluid collections due to underlying SIH is associated with young age (≤55 years old), no underlying diseases, smaller amount of fluid collections (≤22.08 mm of depth), and radiological findings of brain sagging or pseudo‐subarachnoid hemorrhages.